Playing Hide and Seek: How Glycosylation of the Influenza Virus Hemagglutinin Can Modulate the Immune Response to Infection - Michelle D. Tate; Emma R. Job; Yi-Mo Deng; Vithiagaran Gunalan; Sebastian Maurer-Stroh; Patrick C. Reading (Viruses, 2014)
Seasonal influenza A viruses (IAV) originate from pandemic IAV and have undergone changes in antigenic structure, including addition of glycans to the hemagglutinin (HA) glycoprotein. The viral HA is the major target recognized by neutralizing antibodies and glycans have been proposed to shield antigenic sites on HA, thereby promoting virus survival in the face of widespread vaccination and/or infection. However, addition of glycans can also interfere with the receptor binding properties of HA and this must be compensated for by additional mutations, creating a fitness barrier to accumulation of glycosylation sites. In addition, glycans on HA are also recognized by phylogenetically ancient lectins of the innate immune system and the benefit provided by evasion of humoral immunity is balanced by attenuation of infection. Therefore, a fine balance must exist regarding the optimal pattern of HA glycosylation to offset competing pressures associated with recognition by innate defenses, evasion of humoral immunity and maintenance of virus fitness. In this review, we examine HA glycosylation patterns of IAV associated with pandemic and seasonal influenza and discuss recent advancements in our understanding of interactions between IAV glycans and components of innate and adaptive immunity.